(untitled) - Dr. L Jalaja (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Sustainable entrepreneurship has enormous potential and is quickly becoming a key instrument for bringing about positive, long-term change through sustainability-oriented innovation. However, sustainability-oriented start-ups confront a number of unique issues that are not only connected to the creation of a new enterprise, but also to sustainability-related difficulties that necessitate the need for additional resources. Support for such endeavours Start-up accelerators is regarded as one of the most crucial support mechanisms for fledgling businesses. Creative initiatives, including start-ups focused on sustainability. Government through its flagship Startup India Project (w.e.f 2016) has been working to provide a favourable environment to encourage entrepreneurship and ignite the economic growth. It is also working to build an infrastructure for value added e-governance, investments and innovation via higher education. According to research, the development of the startup environment has mostly been concentrated in big cities. (Tier 1) cities and states having significant financial resources, particularly in IT-enabled industries such as ecommerce, transportation, and banking. Small firms outside of metro areas are not fully aware of, or incorporated into, programmes that give different government incentives and tax benefits to entrepreneurs. Inspite of all these, many of the startups face bottlenecks predominantly due to the unstructured and fragmented character of the market, lack of clarity on governmental initiatives and support and lack of infrastructure. Increasing awareness of government efforts and incentives, loan distribution to key industries, boosting outreach and network advantages and simplifying financing and tax concessions for international and domestic investors might all help startups in India.